After the fact : the art of historical detection - Davidson, James West; Lytle, Mark H. (New York : Alfred A. Knopf, 1982)
Under the historians eye, the puzzles of the past turn and reveal themselves. Here are good stories well told, displaying the essential fascination of scholarship in action and what it can accomplish.
Includes bibliographies and index.
Keywords: United States -- Historiography; United States -- History